EKSISTENSI KEADILAN SOSIAL DALAM KEUANGAN PUBLIK ISLAM - Ramadhan Razali; Sutan Febriansyah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2019)
The Conclusion form this research is social justice in Islamic societies can prosper society and advance the economic level of the State. The existence of the principle of social justice can be seen from the instruments of Islamic distribution of interest in equalizing wealth in society. The principle of justice is also contained in the Islamic land tax instrument. Therefore, the bidding instrument in Islamic public finance offered by Abi Ja'far Ibn Nasr al-Dawudi is very relevant to this era. This study uses Adam Smith's taxation theory which says that the principles of taxation are certainty, fairness, economics, and belief. While for the theory of social justice the writer uses the theory of John Rawls which explains about justice must represent the principles of justice and equality. The method used by the author is a qualitative method. Through collecting data and information through literature (library research). As primary data in this study is the book Al-Dawudi, that is Wa b Al-Amwal by Abi Ja'far Ibn Nasr Al-Dawudi. While for secondary data the authors use books related to the theme, namely the thesis or dissertation of journals and information media relating to the theme of this thesis. What was being discussed was discussing history and discussing contemporary Islamic economics.